Creative Cultural Tourism as a New Model for Cultural Tourism - Al-Ababneh, Mukhles; Masadeh, Mousa (Journal of Tourism Management Research, 2019)
The aim of this study is to identify the move from cultural to creative cultural tourism as new model for meeting tourists’ demands for creative experiences. Hence, traditional cultural tourism must reinvent itself as creative tourism for those creative tourists seeking more interactive experiences. This new trend in creative cultural tourism has emerged from the changes in the production of cultural tourist commodities, the skilled tourist activities, and new consumption patterns. Moreover, creative cultural tourism can solve those problems experienced by traditional cultural tourists. A literature review confirmed that a move to creative cultural tourism, or intangible heritage (i.e., linguistic diversity or gastronomy), from tangible cultural attractions (i.e., museums, monuments, and so forth) increases the attractiveness of tourism destinations. In addition, this study explains the transformation from traditional cultural to creative cultural tourism.